Pengaruh Komunikasi Organisasi terhadap Kinerja Tenaga Kesehatan yang Dimediasi oleh Motivasi di RSUD Kota Malang - Gondowahjudi, Lana Emilia; Ratri, Devita Rahmani; Hakim, Lukman (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
The result of preliminary study about the clinical effectiveness of RSUD Malang, the success of effective communication training in Malang Hospital is caused by the lack of motivation owned by health personnel, thus giving the influence of the decreasing of the performance of the health personnel. The purpose of this study is to determine the effect of organizational communication on the performance of health personnels of RSUD Kota Malang, which is assumed to be mediated by motivation. The results showed that organizational communication had a significant positive effect on motivation (original sample = 0,434, value of TStatistics = 6,021); organizational communication has a significant positive effect on the performance of health personnel (original sample = 0.617, T-Statistics = 11.778); motivation has a significant positive effect on the performance of health personnel (original sample = 0.226, T-Statistics = 3,533); and motivation mediate between the influence of organizational communication on the performance of health personnel (Zsobel test = 3.050, value P-Value = 0.002).